The Husband List Book 2 - Evanovich, Janet; Kelly, Dorien (New York : St. Martins Press, 2013)
Pressured by her mother to marry a proper gentleman, Caroline Maxwell reluctantly considers Lord Bremerton while harboring a secret longing for adventure and passion with her brothers world-traveling friend, Jack, whose new money and lack of title render him an unsuitable candidate in her mothers eyes.
"A novel"--Jacket.
Keywords: Young women -- Fiction; Dating (Social customs) -- Fiction; Rich people -- Fiction; New York (N.Y.) -- History -- 1865-1898; Fiction